Heart rate, time-motion, and body impacts when changing the number of teammates and opponents in soccer small-sided games - Torres-Ronda, L.; Gonçalves, B.; Marcelino, R.; Torrents, C.; Vicente, E.; Sampaio, J. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to determine the internal (heart rate) and external load (body load, distance covered, and exertion index) during different types of unbalanced soccer small-sided games (SSGs) in professional (PRO) and amateur (AMA) players. In 2 separated sessions (PRO and AMA), participants played 3 SSG formats (4vs3, 4vs5, and 4v7). Data were analyzed from the fixed team's perspective (4vsX) according to the number of opponents (3, 5 and 7) and from the variable team (3 + Xvs4) according to the teammates (without teammates, 2 and 4 teammates). The time-motion and body impact data were collected using a nondifferential global positioning system with integrated heart rate measurement. Differences in internal and external workload between the game formats were compared using Cohen's dunb effect sizes with 95% confidence intervals. Results reveal that the higher the number of players involved in the task, the lower the internal and external workload. The analysis also showed different teammates and opposition-related trends that need to be considered when planning and monitoring training performance. Playing in low-inferiority (4vs3 and 4vs5) had higher physiologic impact to players than the other higher unbalanced situations. This evidence was similar to both PRO and AMA players; however, the PRO presented higher physical and lower physiological responses across games. Our results suggest that coaches should consider the usage of unbalanced SSG formats to simultaneously facilitate the emergence of defensive and offensive proficient scenarios also representing opportunities to increase the practice workload.